2011
DOI: 10.3109/10520295.2011.590155
|View full text |Cite
|
Sign up to set email alerts
|

Honey as a substitute for formalin?

Abstract: Formalin has long been the standard fixative for clinical routines worldwide. After the Formaldehyde Standard became law in the US in 1987, as a result of increasing concerns about the potential carcinogenicity of formaldehyde, attempts have been made to find safer alternatives. Alcoholic formalin is a useful fixative, because in addition to fixation, dehydration also is begun. For centuries, honey has been known to be an antibacterial agent with the potential to preserve compounds without harmful effects on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…3). Studies by Al-Maaini and Bryant 14 and Ozkan and coworkers 15 showed better staining of connective tissue with honey fixation. The property of this fixation is attributed to the aldehyde hydroxymethyl furfural that forms cross-links with amino acids, similar to formalin.…”
Section: Discussionmentioning
confidence: 95%
“…3). Studies by Al-Maaini and Bryant 14 and Ozkan and coworkers 15 showed better staining of connective tissue with honey fixation. The property of this fixation is attributed to the aldehyde hydroxymethyl furfural that forms cross-links with amino acids, similar to formalin.…”
Section: Discussionmentioning
confidence: 95%
“…Nuclear morphology showed no statistically significant difference between alcoholic formalin (3.25±0.13) and honey (2.83 ±0.2) fixation ( p >0.05). Similarly there was no significant difference among these fixatives with regard to cytoplasmic detail (p>0.05) Even immunohistochemical comparison done in Ozakan N et al [2] study for honey fixed and formalin fixed paraffin embedded tissue with Vimentin and Ki67 showed convincing results. There were no statistically significant differences among the various fixatives compared.…”
Section: Discussionmentioning
confidence: 79%
“…Ozakan N et al [2] study which compared honey with neutral buffered formalin and alcohol formalin various lesion in histopathology. Nuclear morphology showed no statistically significant difference between alcoholic formalin (3.25±0.13) and honey (2.83 ±0.2) fixation ( p >0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously studies were carried out using sugar syrup, jaggery, molasses and honey as an alternative to formalin for fixation [2,6]. Formalin, a chemical used to preserve tissues for biological and histopathological examinations, is added to milk to retain its freshness and prevent it from spoiling [7].…”
Section: Discussionmentioning
confidence: 99%